Proceedings of the 2015 ACM Conference on Special Interest Group on Data Communication 2015
DOI: 10.1145/2785956.2787476
|View full text |Cite
|
Sign up to set email alerts
|

Condor

Abstract: The design space for large, multipath datacenter networks is large and complex, and no one design fits all purposes. Network architects must trade off many criteria to design costeffective, reliable, and maintainable networks, and typically cannot explore much of the design space. We present Condor, our approach to enabling a rapid, efficient design cycle. Condor allows architects to express their requirements as constraints via a Topology Description Language (TDL), rather than having to directly specify netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This not only steepens the learning curve but also makes automation more di cult, as tools must support various syntaxes and semantics [2]. Past studies have shown that inconsistent con guration interfaces are a major source of operational errors and outages [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…This not only steepens the learning curve but also makes automation more di cult, as tools must support various syntaxes and semantics [2]. Past studies have shown that inconsistent con guration interfaces are a major source of operational errors and outages [3] [4].…”
Section: Introductionmentioning
confidence: 99%